Recovery Plan Awareness Among South Florida Land-Use Decision-Makers - Janas Sinclair; Frank Mazzotti; Jocie Graham (Journal of Applied Communications, 2005)
This study identified a challenge for natural resource communication: increasing awareness of species recovery plans among a key audience, local decision-makers. Under the Endangered Species Act, recovery plans are written to conserve threatened and endangered species and their ecosystems. For these plans to be successful, they must be integrated into local land-use decisions. A survey of landuse planners and regulators (N = 59) in the 19 counties of south Florida examined 1) exposure to information about threatened and endangered species, 2) awareness of the South Florida Multi-species Recovery Plan (MSRP), and 3) awareness of local threatened and endangered species. The results indicated decision-makers are receiving relatively little information about threatened and endangered species, have low awareness of the MSRP, and are only moderately aware of which threatened and endangered species occur in their counties. There is a need for better communication with local land-use decision-makers to increase awareness of recovery plans, the information they contain, and how to access them. Decisionmakers also reported being pressed for time, needing information that pertains specifically to their county, and having concerns about the quality of the available information. Recommendations for message strategy include developing condensed versions of the plan, organizing information by county, and providing information to help decision-makers evaluate the utility and limitations of recovery plan information and make appropriate interpretations. Future research should examine how best to communicate with decisionmakers in the context of recovery planning and other agricultural and natural resources issues.